Selective colorimetric and fluorimetric detection of cyanide in aqueous solution using novel heterocyclic imidazo-anthraquinones - Batista, Rosa Maria Ferreira (2014)
Novel receptors based on imidazo-anthraquinone system containing thiazole, (benzo)furan, thiophene and imidazole heterocycles at position 2 were synthesized. The photophysical properties of compounds 1-8 were studied by UV-vis and fluorescence spectroscopy in acetonitrile. All anthraquinone derivatives exhibited great selectivity for the cyanide anion over other anions in acetonitrile/water (9:1) solution showing a distinct colour change from yellow to orange and the fluorescence emission was switched “off”. The binding stoichiometry between the receptors and the anions was found to be 1:1. Moreover, chemosensors 1-8 exhibit a high sensitivity being capable to detect cyanide in very low concentrations (below 4 microM).